Mise en scène as a feminine textual body : making meaning in new plays - Stopford, Clare (Department of Drama, 2015)
This study proceeds from research I have conducted through autobiographical writing, into my experiences of directing untried play texts for first performance. The question of ownership of the meaning conveyed by the play in performance, in the negotiated space between the writer and the director, provides the frame for this discussion. Who has the right of ownership over meaning, and in times of dissension about meaning, whose meaning should prevail? Since it is the writer's first opportunity to see his or her play on the stage, it would seem that the ethics of the situation favour the writer. However, if the director's modality is unconscious, intuitive and 'felt' as mine is, the best and most ethical path to follow may be hard to discern by both director and writer. At the same time, the intuitive modality of the director may be destabilized by the presence of the writer. Within this conundrum my focus is on identifying, exploring and considering the director's modality, which I have identified as 'feminine', a term which in this text favours sexual differentiation as a feminist strategy for the re-creation and re-inscription of woman within a male dominated signifying system. Rosi Braidotti's evocation of Cixous' creative writing as a 'feminine textual body' in resistance to woman as 'non-said', and as procreation of woman as a subject, provides the inspiration for the conceptualization of mise en scène as a feminine textual body. Using Green Man Flashing written by Mike Van Graan and directed by me in 2004, and Lara Foot's Reach that I directed in 2007, as case studies, I consider, as well as assess the impact, of my feminine directorial modality on these two performance texts. I am interested in how meaning is made from inside the feminine modality, what meaning is made, and finally, how the feminine modality is affected by the material circumstances in which these two plays were rehearsed. My aim is to extend the feminine modality into the style of it's dissemination by taking the reader into the 'feeling' of the modality in a style of writing that embodies the personal, intimate, intuitive qualities it invokes. I also take a more analytical view, assessing the efficacy of the feminine modality by using the lenses of materialist feminists such as Dolan and Diamond, as well as Irigaray's 'relational alterity'. The outcome of this exploration is that the feminine modality is both a solution and a problem, depending on material circumstances. Its paradoxical nature requires a third space in which it can stabilize, and yet remain accessible to the unconscious.